Coache's verbal reactions and physiological responses to critical game incidents - Knight, C. J.; Kennedy, M. D.; Holt, N. L. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: The current study sought to examine how coaches` verbal comments and heart rates (HR) changed in relation to game circumstances in high performance sport. Methods: Three coaches (a head coach - HC, and 2 assistants - AC1 and AC2) of a University Hockey team participated in this study. Data were collected at 4 home games over 2 weekends. HR data, verbal comments, and critical incidents for each game were recorded. Coaches` verbal comments were recorded using a Dictaphone with a lapel-microphone attached. HR in beats/min (bpm) was recorded with Suunto T6 watches/Team pod (Suunto, Vaanta Finland). Critical incidents were documented in real time and confirmed from game recordings. Following each game verbal comments were transcribed and time stamped. Comments were then coded against the categories of the Coach Behavior Assessment System (Smith et al., 1977). Results: Over the four games, Mean/SD HR for periods 1, 2, 3 was 109/7, 83/3, 79/2 for HC, AC1, AC2 respectively and the mean HR was not different between periods (HC: 111/6, 108/9, 108/8; AC1: 83/5, 82/4, 82/1; AC2: 78/2, 79/2, 81/2 for periods 1, 2, 3 respectively). Mean Overtime and Shootout HR was 5 and 2 bpm respectively less than mean period HR. As a percentage of age predicted HRmax coaches mean period HR were: 63%, 48% and 45% (HC, AC1, AC2). The HR response to the critical game instance "goals scored" was 110, 82, 80 and to "penalties" HR was 110, 82, 80 for for HC, AC1, AC2 respectively. Verbal reactions to goals and penalties differed between the three coaches. The HC tended to react to goals scored with reinforcement and general encouragement but was often silent in reaction to goals conceded. In contrast, ACs showed less consistent reactions to goals, although general encouragement was common when goals were scored and general commentary provided when goals were conceded. Organization and mistake-contingent tactical instruction were common reactions to home team penalties, whereas organization, reinforcement, and general encouragement were more often heard in reaction to away team penalties. Discussion: Coaches experience psychophysiological responses to competition, indicating that watching sport can induce stress-related responses in coaches. However whereas verbal responses changed to critical instances HR was not altered by critical instances of "goals" or "penalties". Thus only verbal responses change with critical incidents, likely in an attempt to increase or reduce the likelihood of a certain incident occurring again. Although further investigation is required, it seems the stress related response of increased overall HR is not influenced by occurrences to critical game incidents despite the clear change in verbal comments by coaches to these critical incidents.